Republic of Panama : Public Expenditure and Financial Accountability - World Bank; Inter-American Development Bank (World Bank, Washington, DC, 2014)
Panama's public financial management (PFM) system displays several strengths with respect to the fiscal position, debt management, and payroll administrative controls, but from a systemic perspective budget preparation and budget credibility issues undermine the efficiency of sectoral investment plans and make it difficult to advance on other improvements in the public sector. An efficient and transparent allocation of budgetary resources allows the government to achieve value for money in delivering public services. This assessment is undertaken at the request of the Government of Panama (GoP) which is in the process of reforming and modernizing its public finances, and is therefore interested in establishing both a baseline for future PFM performance measures and the degree of management alignment to internationally accepted best practices. The public expenditure and financial accountability (PEFA) methodology provides relevant information on current management and will allow establishment or adjustment of a reform strategy to improve PFM quality. This PEFA assessment provides a reference and a baseline for two projects and a baseline for the GoP to measure progress of the current reform. The projects are: (i) the program to strengthen fiscal management financed by Inter-American Development Bank (IADB), and (ii) the enhanced public sector efficiency technical assistance loan financed by World Bank (WB).